Pembaharuan hukum acara peradilan agama dilengkapi format formulir berpekara / Ahmad Mujahidin ; editor Zaenudin A. Naufal. - AHMAD MUJAHIDIN, 1968-; Zaenudin A. Naufal (Ghalia Indonesia, 2014)
xii, 370 hlm. : ilus. ; 25 cm [3 eks.]